Extreme Drought Assessment in Sumatra-Indonesia Using SPI and EDI - Suhadi; Iskhaq Iskandar; Supari; Muhammad Irfan; Hamdi Akhsan (Science and Technology Indonesia, 2023)
Even though Sumatra is very vulnerable to the effects of drought, research identifying drought on this island is very limited, especially extreme drought. This research was conducted to identify extreme drought in Sumatra using the Standardized Precipitation Index (SPI) and the Effective Drought Index (EDI). This study uses precipitation data from the Indonesian Meteorology, Climatology and Geophysics Agency (BMKG) and Global Precipitation Climatology Center (GPCC) reanalysis data. The composite indices were conducted to discover some phenomena that cause the drought based on El Niño and positive Indian Ocean Dipole (IOD) events. The results showed that the El Niño and positive IOD phenomena were more likely to influence extreme droughts. However, the droughts in 2014 and 2008 tended to be influenced by the negative Sea Surface Temperature anomaly (SSTA). The spatial analysis results show that the areas that experience extreme drought more often are the west coast of Sumatra (except Aceh province), especially based on SPI12 and EDI. The composite indices results show that the drought that occurred in Aceh province was more influenced by the El Niño phenomenon in the December-January-February (DJF) period and the positive IOD in the June-July-August (JJA) – September-October-November (SON) period. In addition, Aceh province is an area that is not affected by El Niño-positive IOD, especially during the SON-DJF period. These results can be used to mitigate drought, especially when El Niño-positive IOD phenomena cause it.